Clive Staples Lewis : a dramatic life - Griffin, William, 1935- (Harper & Row, 1986)
"Christian apologist, literary historian, scholar, critic, writer of science fiction and children's books, he was one of the more prolific authors of his time," read the London Times obituary of C.S. Lewis after his death on November 22, 1963. "As a Christian writer his influence was marked; he caught and held the attention of those usually apathetic to religion, of lapsed churchgoers and of people who liked to think themselves agnostics; ... he made religious books bestsellers and, in a nice sense, fashionable." This is an imaginative biography that recreates C.S. Lewis's life with striking impact--a narrative account in which Lewis speaks for himself at almost every moment and incident. A thousand scenes, some very short, all in chronological order, flash by like frames of celluloid on a silver screen. Better than a feature film, this book brings to life a vivid and multifaceted portrait of Lewis. "He was a poet as contemporary as Auden and a versifier as funny as Gilbert," Griffin writes. "He was a satirist as slashing as Waugh and a social critic as clever as Coward; he was a scholar as sharp as Leavis and a mythologer as wise as Tolkien. He was a broadcaster with enormous audience and a correspondent of staggering proportion ... Emerging from the narrative is an active, energetic man who looked like a farmer but talked like a philosopher, who would as soon lolligag in fairydom as joust in intellectual lists, who relished the love of friendship, was surprised by the love of a woman, and cultivated the love of God."--Abebooks